2008
DOI: 10.1158/0008-5472.can-08-1489
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccination Controls Her-2+ Tumors that Are Refractory to Targeted Therapies

Abstract: Her-2/neu + tumor cells refractory to antibody or receptor tyrosine kinase inhibitors are emerging in treated patients. To investigate if drug resistant tumors can be controlled by active vaccination, gefitinib and antibody sensitivity of four neu + BALB/c mouse mammary tumor lines were compared. Significant differences in cell proliferation and Akt phosphorylation were observed. Treatment-induced drug resistance was associated with increased chromosomal aberrations as shown by spectral karyotyping analysis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…The effectiveness of the MSC/Neu vaccines was tested in transplantation models employing TUBO cells, derived from NeuT transgenic mice, and D2F2/neu cells, generated by transfection of D2F2 mammary tumor cells with a neuexpressing vector (14). It was previously shown in vivo that TUBO cell growth was inhibited by anti-neu antibody and CTL responses, whereas D2F2/neu cell regression depended on the induction of strong CTL responses (16). Using a prophylactic protocol, we observed that immunization with allogeneic MSC/Neu protected against TUBO but not against D2F2/ neu cell challenges (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of the MSC/Neu vaccines was tested in transplantation models employing TUBO cells, derived from NeuT transgenic mice, and D2F2/neu cells, generated by transfection of D2F2 mammary tumor cells with a neuexpressing vector (14). It was previously shown in vivo that TUBO cell growth was inhibited by anti-neu antibody and CTL responses, whereas D2F2/neu cell regression depended on the induction of strong CTL responses (16). Using a prophylactic protocol, we observed that immunization with allogeneic MSC/Neu protected against TUBO but not against D2F2/ neu cell challenges (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…D2F2 cells were derived from a mouse mammary tumor that arose in a BALB/c hyperplastic alveolar nodule. D2F2/neu cells (16) were obtained from D2F2 cells after transfection with pCMV/ neu encoding the transforming rat neu, and were kindly provided by Dr. Wei-Zen Wei (Wayne State University, Detroit, MI). Cell lines were not authenticated.…”
Section: Cell Lines and Primary Dendritic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, conventional DNA vaccines have little therapeutic efficacy against solid tumors (22,23). To determine the therapeutic effects of sPD1-p24 fc /EP, mice were first inoculated subcutaneously with the lethal dose of AB1-GAG cells followed by sPD1-p24 fc /EP, p24 fc /EP or sham vaccination the next day and every 2 weeks for four times (Fig.…”
Section: Therapeutic Cure Of Mesothelioma By Vaccine-elicited Immune mentioning
confidence: 99%
“…HER2/neu has been targeted using polynucleotide or DNA vaccine strategies involving both syngeneic and xenogeneic sequences, the latter to improve the magnitude of elicited immune responses [246][247][248][249][250][251][252][253][254], in prime boost strategies combining DNA vaccines with viral vector-based vaccines [255] and with gene-modified allogeneic cellular vaccines (NCT00095862) [256]. Viral vector vaccine strategies using adenovirus vectors [257][258][259][260], alphavirus vectors [212,213,261], vaccinia virus vectors (NCT00485277 and NCT01152398), vesicular stomatitis virus [262] and polyoma virus systems [263,264] have all been used to elicit anti-HER2/neu immune responses.…”
Section: Her2/neu Antigen-specific Immunotherapymentioning
confidence: 99%